1982
DOI: 10.1007/bf00442326
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal anthropometric measurements in patients with growth hormone deficiency. Effect of human growth hormone treatment

Abstract: The effect of human growth hormone (6IU/m2 twice weekly i.m.) on standing, sitting, and subischial leg height, on arm length, head circumference, fronto-occipital and biparietal head diameter, bi-iliac (pelvis) and bihumeral (shoulder) width, body weight, triceps and subscapular skinfold thickness, and upper arm and calf circumferences was studied longitudinally over a period of 2 years in 37 prepubertal growth hormone deficient patients (29 boys, 8 girls). Thirteen of them had isolated growth hormone deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

1986
1986
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 21 publications
4
10
0
Order By: Relevance
“…The BMI decreases especially in the first 6 months and after 12 months it increases again, but not completely to the initial value. This pattern of initial decrease followed by an increase parallels previous findings of change in skinfold thicknesses during GH therapy in GHD children [7, 8, 9]. It was shown that the decrease in skinfold thickness shows a nadir after 9 months of GH therapy [8].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The BMI decreases especially in the first 6 months and after 12 months it increases again, but not completely to the initial value. This pattern of initial decrease followed by an increase parallels previous findings of change in skinfold thicknesses during GH therapy in GHD children [7, 8, 9]. It was shown that the decrease in skinfold thickness shows a nadir after 9 months of GH therapy [8].…”
Section: Discussionsupporting
confidence: 87%
“…Because GHD is associated with a truncal pattern of fat distribution and with increased skinfold thicknesses [7, 8, 9], mild to moderate overweight is usually thought to be a feature of GHD. However, our study shows that GHD children are on the average not heavier than normal children if BMI is used as a parameter of overweight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this group, as well as in other studies in young children with GHD [33, 34, 35], the GH effect was more appropriately reflected by height gain, which, in our study, was equivalent to that of the prepubertal overweight group, and continued to increase during the 4th year of GH treatment. As the increase in hand and foot length was similar to the height increase in all groups, the prepubertal children over 3 years of age no longer had small hands and feet and all body proportion parameters were balanced, as known in GHD patients during therapy [36]. …”
Section: Discussionmentioning
confidence: 99%
“…Because of a similar increase in hand and foot length and height, these children no longer have small hands and feet and all body proportion parameters are balanced (fig. 1) [69], as happens in treated GHD patients [76]. …”
Section: Argument 6: Catch-up Growth With Human Gh Therapy In Pwsmentioning
confidence: 99%